2011
DOI: 10.4236/msa.2011.210184
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations of Ti-Based Binary Shape Memory Alloys

Abstract: The electronic structure and ground state properties of TiX (X = Fe, Ni, Pd, Pt and Cu)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
4
2
0
Order By: Relevance
“…Furthermore, it is observed the EF cuts TDOS of Ti50Fe50, Ti50Ru50 and Ti50Os50 near the centre of the pseudogap, indicating that B2 remain stable with no prospect of phase transition, from both codes. This observation is in good agreement with other work reported in the literature [32]. It is revealed that the VASP code finds Ti50Ru50 and Ti50Ni50 while CASTEP finds Ti50Fe50 and Ti50Ir50 to be the most stable and unstable B2 compounds at 0 K, respectively.…”
Section: Electronic Propertiessupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, it is observed the EF cuts TDOS of Ti50Fe50, Ti50Ru50 and Ti50Os50 near the centre of the pseudogap, indicating that B2 remain stable with no prospect of phase transition, from both codes. This observation is in good agreement with other work reported in the literature [32]. It is revealed that the VASP code finds Ti50Ru50 and Ti50Ni50 while CASTEP finds Ti50Fe50 and Ti50Ir50 to be the most stable and unstable B2 compounds at 0 K, respectively.…”
Section: Electronic Propertiessupporting
confidence: 92%
“…However, some level of discrepancy was found between the two codes on other compounds such as Ti50Fe50, Ti50Rh50, Ti50Pd50, Ti50Ir50 and Ti50Pt50, with Ti50Fe50 being the worst. The results from the current work were also plotted against some theoretical values reported in the literature [26,32,36,37,38,39], and a good match is found in most binary compounds, indicating the level of accuracy.…”
Section: Ti50pt50supporting
confidence: 57%
See 2 more Smart Citations
“…Amongst the investigated B2 compounds, the heat of formation value of Ti 50 Ir 50 was found to be the most thermodynamically stable indicated by the lowest value of À0.913 eV/atom. The reported heat of formation results were found to be in accordance with other data in literature [51,52,[55][56][57][58].…”
Section: Structural and Thermodynamic Stabilitysupporting
confidence: 90%